2015 proceedings of the National Heart, Lung, and Blood Institute's State of the Science in Transfusion Medicine symposium. Issue 9 (10th August 2015) - Spitalnik, Steven L.; Triulzi, Darrell; Devine, Dana V.; Dzik, Walter H.; Eder, Anne F.; Gernsheimer, Terry; Josephson, Cassandra D.; Kor, Daryl J.; Luban, Naomi L. C.; Roubinian, Nareg H.; Mondoro, Traci; Welniak, Lisbeth A.; et al.
Abstract : On March 25 and 26, 2015, the National Heart, Lung, and Blood Institute sponsored a meeting on the State of the Science in Transfusion Medicine on the National Institutes of Health (NIH) campus in Bethesda, Maryland, which was attended by a diverse group of 330 registrants. The meeting's goal was to identify important research questions that could be answered in the next 5 to 10 years and which would have the potential to transform the clinical practice of transfusion medicine. These questions could be addressed by basic, translational, and/or clinical research studies and were focused on four areas: the three "classical" transfusion products (i.e., red blood cells, platelets, and plasma) and blood donor issues. Before the meeting, four working groups, one for each area, prepared five major questions for discussion along with a list of five to 10 additional questions for consideration. At the meeting itself, all of these questions, and others, were discussed in keynote lectures, small‐group breakout sessions, and large‐group sessions with open discourse involving all meeting attendees. In addition to the final lists of questions, provided herein, the meeting attendees identified multiple overarching, cross‐cutting themes that addressed issues common to all four areas; the latter are also provided. It is anticipated that addressing these scientific priorities, with careful attention to the overarching themes, will inform funding priorities developed by the NIH and provide a solid research platform for transforming the future practice of transfusion medicine.